WIBDI, the broker linking smallholder farmers in the Pacific to markets - Apa, Taaloga (Technical Centre for Agricultural and Rural Cooperation, 2019)
Taaloga Apa, Senior Programme Manager at the Women In Business Development Incorporated (Samoa) explains how the organisation is supporting smallholder farmers in getting into organic farming, getting their farms certified as organic and linking them to local, regional and global markets.